Effect of moisture and temperature on the extrudate properties of milkfish (Chanoschanos) feed - Raffic Ali, S. Syed; Ambasankar, K.; Balachandran, S.; Ramachandran, K. (Indian Journal of Fisheries, 2019)
The present study evaluated the effect of varying levels of moisture and temperature on the extrudate properties of the milkfish (Chanos chanos) feed containing 31.49% protein and 4.71% lipid. Two trials were conducted in a pilot scale twin screw extruder using 3 mm die. In the first trial, the effect of temperature on extrudate properties was studied at five different temperatures viz., 80-90, 90-100, 100-110, 110-120 and 120-130ºC. The results revealed that the temperature levels of 100-110, 110-120 and 120-130ºC resulted in significantly (p<0.05) lower bulk density (BD) of the extrudate than at 80-90 and 90-100ºC. Significantly (p<0.05) lower water solubility index (WSI) was recorded at 100-110ºC, while further increase in temperature failed to show further reduction in water solubility. The pellet durability index (PDI) and expansion ratio (ER) showed a non-significant difference among the extrudates at 100-110, 110-120 and 120-130ºC. In the second trial, the effect of additional moisture on the extrudate was evaluated by including water at 20, 25, 30 and 35% and the results revealed that 30% moisture addition resulted in significantly (p<0.05) lower BD, WSI and PDI of the extrudate than the other levels. The highest moisture level of 35% led to difficulty in operation while the lower levels from 25% failed to produce floating pellets. Results of this study infers that 30% moisture addition and a temperature of 100-110ºC is optimal for production of water stable floating milk fish feeds.